2013
DOI: 10.1002/chem.201301809
|View full text |Cite
|
Sign up to set email alerts
|

Decarboxylative Palladium(II)‐Catalyzed Synthesis of Aryl Amidines from Aryl Carboxylic Acids: Development and Mechanistic Investigation

Abstract: A fast and convenient synthesis of aryl amidines starting from carboxylic acids and cyanamides is reported. The reaction was achieved by palladium(II)-catalysis in a one-step microwave protocol using [Pd(O2CCF3)2], 6-methyl-2,2′-bipyridyl and trifluoroacetic acid (TFA) in N-methylpyrrolidinone (NMP), providing the corresponding aryl amidines in moderate to excellent yields. The protocol is very robust with regards to the cyanamide coupling partner but requires electron-rich ortho-substituted aryl carboxylic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 63 publications
3
25
0
1
Order By: Relevance
“…Besides nitriles, cyanamides too are potential candidates for the 1,2‐addition reactions. Similar instances of 1,2‐addition in cyanamides are reported for the palladium‐catalyzed synthesis of arylamidines using aryltrifluoroborates14a and very recently using arylcarboxylic acids14b as the aryl precursor (path b, Scheme ). While arylcarboxylic acids serve as latent aryl sources, the α‐oxocarboxylic acids are sources for the acyl/aroyl moiety in various coupling reactions 9a.…”
Section: Introductionsupporting
confidence: 67%
See 1 more Smart Citation
“…Besides nitriles, cyanamides too are potential candidates for the 1,2‐addition reactions. Similar instances of 1,2‐addition in cyanamides are reported for the palladium‐catalyzed synthesis of arylamidines using aryltrifluoroborates14a and very recently using arylcarboxylic acids14b as the aryl precursor (path b, Scheme ). While arylcarboxylic acids serve as latent aryl sources, the α‐oxocarboxylic acids are sources for the acyl/aroyl moiety in various coupling reactions 9a.…”
Section: Introductionsupporting
confidence: 67%
“…The in situ hydrolysis (from the water contained in commercial grade DCE) of intermediate ( D ) results in the formation of α‐ketoamide. The formations of the intermediate species ( B ), ( C ) and ( D ) have been detected by the ESI/MS analysis of reaction aliquot (see the Supporting Information) 12b,14b. Thus, (NH 4 ) 2 S 2 O 8 plays the dual role of an oxidant as well as a radical initiator in this reaction.…”
Section: Resultsmentioning
confidence: 94%
“…117 Subsequently, Larhed showed that nitriles could be replaced with cyanimides to generate aryl amidines. 118…”
Section: Short Review Syn Thesismentioning
confidence: 99%
“…In a number of cases, DFT calculations have been used to shed insights into the steps associated with these protodecarboxylation reactions (Goossen&Rodriguez et al, 2010;Xue et al, 2011). While it is not possible to make a direct comparison between the protodecarboxylation reactions of group 10 carboxylate complexes that we have studied in the gas phase (Woolley et al, 2013; and related systems in the condensed phase, for the second decarboxylation step, DFT calculations highlight that a difference between the gas phase and solution is that in solution coordinating ligands and/or solvent molecules need to be considered, and that part of the energy cost for decarboxylation maybe due to the energy required to lose the coordinated ligand/solvent molecule to free up a vacant coordination site for decarboxylation (Zhang et al, 2010;Dickstein et al, 2013;Rydfjord et al, 2013). In the gas phase, these coordinating ligands and/or solvent molecules are generally missing.…”
Section: Author Manuscriptmentioning
confidence: 99%